AB0007 Incidence and Functional Relevance of IL-23 Receptor Gene Polymorphisms in Ankylosing Spondylitis. (10th June 2014) - Fessler, J.; Stradner, M.; Peischler, D.; Graninger, W.; Hermann, J.
Abstract : Background: Interleukin-23 (IL-23) signaling is involved in Th17 immune response and thus in the pathogenesis of ankylosing spondylitis (AS). Objectives: The purpose of this study was to investigate the functional relevance of single nucleotide polymorphisms (SNP) in the IL-23 receptor (IL-23R). Methods: 105 patients with AS according to the modified New York criteria were prospectively enrolled into the study. Blood was drawn from all individuals and DNA was extracted to determine the SNPs rs 10889677 (SNP1), rs 11209026 (SNP2), rs 11465804 (SNP3) and rs 1343151 (SNP4) by polymerase chain reaction. To test functional relevance of the SNPs we performed intracellular flow cytometry and stained PBMCs with anti-CD3, CD4, CD8, IL-23R, pSTAT-3 and IL-17A. Phosphorylation of STAT-3 (pSTAT-3) following IL-23 stimulation (100ng/ml) and the prevalence of Th17 cells were assessed. Results: We detected homozygote carriers of SNP1 in ten (9.5%) and SNP4 in four (3.8%) patients of our cohort. These patients were wildtype (WT) for the other SNPs tested. We found no homozygote carriers of the SNPs 2 and 3. Fifteen SpA patients were WT for all four SNP tested and served as control group. The frequency of IL-23R + CD4 T cells was significantly increased in the SNP1 group (median 37.3 [27.9-52.7] vs. 25.6 [16.1-38.1], p=0.05) but not in the SNP4 group (32.4 [29.3-34.9], p=0.248). IL-23 (100ng/ml) stimulation of PBMCs induced phosphorylation of STAT3 in the SNP1 group (2.2 [1.7-4.5] vs. 1.3 [0.4-2.7], p=0.087) but not in the SNP4 group compared to WT (1.7 [0.7-2.6], p=0.715). In addition, patients with SNP1 (1.2 [0.8-1.4], p=0.015) but not with SNP4 (1.1 [0.6-1.2], p=0.162) exhibit significantly elevated levels of Th17 cells after stimulation with OKT-3 compared to WT (0.6 [0.5-0.9]). Conclusions: The SNP rs 10889677 increases Il-23R abundance in CD4 + T cells and fosters Th17 response in patients with ankylosing spondylitis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2087